Penanganan Eritema pada Pengunaan Resin Akrilik Swapolimerisasi - Dewi Ayu Ceasarina Taufik; Atia Nurul Sidiqa (Jurnal Material Kedokteran Gigi, 2021)
This case report reports a 67 year old male patient who came with complaints that the front teeth of the lower jaw felt painful and uncomfortable when speaking since 1 week ago, there was an acrylic resin made not by dentist since 1 month ago. The acrylic resin was made because patients complained there was a tooth had loose and broken. The results showed that there was acrylic resin covering the lingual, labial, and incisal regions of teeth 34-44 and covering dental root retained 31 and 42. Self curing denture made not by dentist since 1 month ago. The treatment plan that will be carried out is the removal of the acrylic resin covering the teeth 34-44 and dental root retained 31 and 42, with the next treatment extracting dental root retained 31 and 42. Eythema areas in the gingival region 34-44 were depressed by acrylic resin. After one week control, the erythema area was gone and the gingival region 34-44 looked much healthier than before.